Psychosocial stress is positively associated with body mass index gain over 5 years: Evidence from the longitudinal AusDiab study. (13th June 2013) - Harding, Jessica L; Backholer, Kathryn; Williams, Emily D; Peeters, Anna; Cameron, Adrian J; Hare, Matthew JL; Shaw, Jonathan E; Magliano, Dianna J
<x xml:space="preserve">Abstract</x> Objective Emerging evidence suggests that psychosocial stress may influence weight gain. The relationship between stress and weight change and whether this was influenced by demographic and behavioral factors was explored. Design and Methods A total of 5, 118 participants of AusDiab were prospectively followed from 2000 to 2005. The relationship between stress at baseline and BMI change was assessed using linear regression. Results Among those who maintained/gained weight, individuals with high levels of perceived stress at baseline experienced a 0.20 kg/m2 (95% CI: 0.07‐0.33) greater mean change in BMI compared with those with low stress. Additionally, individuals who experienced 2 or ≥3 stressful life events had a 0.13 kg/m2 (0.00‐0.26) and 0.26 kg/m2 (0.14‐0.38) greater increase in BMI compared with people with none. These relationships differed by age, smoking, and baseline BMI. Further, those with multiple sources of stressors were at the greatest risk of weight gain. Conclusion Psychosocial stress, including both perceived stress and life events stress, was positively associated with weight gain but not weight loss. These associations varied by age, smoking, obesity, and multiple sources of stressors. Future treatment and interventions for overweight and obese people should consider the psychosocial factors that may influence weight gain.